2009
DOI: 10.1016/j.ajhg.2009.03.018
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsense Mutation in COQ9 Causes Autosomal-Recessive Neonatal-Onset Primary Coenzyme Q10 Deficiency: A Potentially Treatable Form of Mitochondrial Disease

Abstract: Coenzyme Q(10) is a mobile lipophilic electron carrier located in the inner mitochondrial membrane. Defects of coenzyme Q(10) biosynthesis represent one of the few treatable mitochondrial diseases. We genotyped a patient with primary coenzyme Q(10) deficiency who presented with neonatal lactic acidosis and later developed multisytem disease including intractable seizures, global developmental delay, hypertrophic cardiomyopathy, and renal tubular dysfunction. Cultured skin fibroblasts from the patient had a coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
187
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(195 citation statements)
references
References 40 publications
7
187
0
1
Order By: Relevance
“…6,11 In mice, this metabolite was identified as 6-demethoxy ubiquinone 9 . Detailed human studies are lacking so far.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6,11 In mice, this metabolite was identified as 6-demethoxy ubiquinone 9 . Detailed human studies are lacking so far.…”
Section: Resultsmentioning
confidence: 99%
“…The case, together with the description of Duncan et al, places COQ9 deficiency among the most severe forms of CoQ 10 metabolism disorders, comparable to descriptions in patients with defects in COQ2 or COQ4. 6,13,14 However, further clinical descriptions will be required to evaluate the specific clinical spectrum of patients with COQ9 mutations. As suggested by Duncan et al, 6 CoQ 10 treatment might be helpful in COQ9-deficient children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, and importantly, Montini et al reported that pre-symptomatic treatment with high doses of coenzyme Q 10 was associated with an excellent clinical outcome in a patient with COQ2 mutations, with no progression of renal disease and no evidence of neurological dysfunction [15]. Renal tubulopathy was noted in the only patient reported with COQ9 mutation to date [16].…”
Section: Nuclear-encoded Mitochondrial Diseasementioning
confidence: 99%